Fisheries bycatch reduction within the least-cost biodiversity mitigation hierarchy: Conservatory offsets with an application to sea turtles. (July 2018) - Squires, Dale; Restrepo, Victor; Garcia, Serge; Dutton, Peter
Abstract: This paper considers fisheries bycatch reduction within the least-cost biodiversity impact mitigation hierarchy. It introduces conservatory offsets that are implemented earlier in the biodiversity impact mitigation hierarchy than conventional compensatory offsets used as instruments of last resort. The paper illustrates implementation in an on-going sea turtle conservation programme by the International Seafood Sustainability Foundation. Highlights: Bycatch reduction within the biodiversity impact mitigation hierarchy. Least-cost (cost-effective) bycatch reduction. Conservatory offsets used within first 3 steps of the mitigation hierarchy and not as last resort. Sea turtle conservatory offsets projects of International Seafood Sustainability Foundation.